Smoking‐related violence in a mental health setting following the implementation of a comprehensive smoke‐free policy: A content analysis of incident reports. (12th September 2019) - Spaducci, Gilda; McNeill, Ann; Hubbard, Kathryn; Stewart, Duncan; Yates, Mary; Robson, Deborah
Abstract: Smoke‐free policies in mental health settings are important to protect health but are often impeded by staff concerns that physical violence may increase. We aimed to address the literature gap about the frequency, nature, and management of physical violence in relation to smoking. We compared the antecedents and containment of smoking‐related incidents of physical violence over a two‐year period, (12 months when an indoor‐only smoke‐free policy was in place, followed by 12 months after a new comprehensive smoke‐free policy was introduced) using incident reports completed by staff in a large mental health organization in London, UK. Sixty‐one smoking‐related incidents occurred during the indoor‐only smoke‐free policy period; 32 smoking‐related incidents occurred during the comprehensive smoke‐free policy. We identified four antecedent categories for physical violence: i) patient request to smoke denied by staff; ii) during a supervised smoking break; iii) staff response to a patient breach of the smoke‐free policy iv) asking for, trading or stealing smoking materials. The antecedent pattern changed across the two policy periods, with fewer incidents of denying a patient's request to smoke and a greater number of incidents involving staff responding to breaches occurring after the introduction of the comprehensive smoke‐free policy. The prohibition of smoking breaks removed this source of violence. Timeout and PRN medication were the most common containment interventions. Understanding the context of smoking‐related violence may inform clinical guidelines about its prevention and management.